Analysis of ultraviolet and thermal degradations of four common microplastics and evidence of nanoparticle release - Hernandez, Laura M.; Grant, Joel; Fard, Parvin Shakeri; Farner, Jeffrey M.; Tufenkji, Nathalie (Journal of hazardous materials letters, 2023)
Many environmental factors affect the breakdown of plastics in aquatic environments, including exposure to ultraviolet (UV) irradiation and elevated environmental temperatures. More studies are needed to understand how these stressors contribute to plastic degradation, resulting in the release of smaller plastic particles. We studied the impact of environmentally relevant UV and temperature (37 °C) weathering of four high-production volume plastics (polystyrene, polypropylene, low-density polyethylene, and high-density polyethylene) suspended in water. Particle release was detected, characterized by scanning electron microscopy (SEM), and nanoparticles were quantified by nanoparticle tracking analysis (NTA). Weathering resulted in the release of micro- and nanoparticles that exhibited a plastic signature corresponding to the parent microplastic. Nanoparticle release is broadly correlated with an increase in the carbonyl index of the parent microplastic. Aged microplastics were characterized for physical and chemical changes. The impact of weathering on microplastic surface hardness and polymer oxidation depended on material type and environmental factors. Few to no particles were observed in controls, including controls that contained microplastics at 4 °C in dark conditions, highlighting the importance of weathering stimuli in particle release. These results show that plastic degradation needs to consider both the parent microplastic and the smaller particles that are formed. [Display omitted] •Four common plastics are degraded with ultraviolet irradiation and high temperature.•Commonly used plastics release micro- and nanoparticles when weathered.•Spectroscopy showed increased surface oxidation in some plastics after weathering.•Extent of plastic degradation depends on both weathering mechanism and material.